Sodium content of bread from bakeries and traditional markets in Maputo, Mozambique - Silva, Vânia (2015)
Objective The Na content of bread is one of the most common targets of initiatives to reduce Na intake worldwide. Assessing the Na content of staple foods is of major relevance in Mozambique, given the high burden of hypertension in this setting. We aimed to estimate the Na content of white bread available in different bakeries and markets in Maputo. Design A cross-sectional study of the Na content of white bread available for sale at twenty-five bakeries and markets in Mozambique. Flame photometry was used to quantify the Na content of the bread. The percentage of samples meeting manufacturer Na targets from South Africa and six countries from other regions, selected as benchmarks, was computed. Setting Maputo, Mozambique. Subjects Three loaves of white bread from each selected bakery/market. Results The mean Na content of bread was 450·3 mg/100 g (range: 254·9-638·3 mg/100 g), with no significant differences between bakeries and traditional markets. Most samples (88 %) did not meet the regulation in South Africa (≤380 mg/100 g). When considering the targets from other countries (range: ≤360-550 mg/100 g), the prevalence of non-compliance varied between 8 % and 92 %. There were no significant differences in the price of bread with Na content below and above the targets. Conclusions The content of Na in bread varies widely in Mozambique, reaching high values in a high proportion of the bakeries and markets in Maputo. Measures to regulate the Na content in bread may contribute to a reduction in Na intake and improved health at the population level.